Characterization of Aflatoxin B1 Biomarkers as Preference for Antitoxin Candidates for Biosensors for Halal Food Supply - Mohammad Sukmanadi1 , Retno Sri Wahjuni 2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The fungus grows on various types of food and feed, its growth will cause damage, including damage toflavor, color, softening, and the formation of toxic compounds. The damage is because the fungus producesextracellular enzymes that break down certain compounds in food and feed, and produce toxic secondarymetabolites, called mycotoxins. Fungal contamination requires serious attention, not only because it causesdamage to food and feed but is related to the potential of the fungus to produce mycotoxins and formconidia that are pathogenic or allergic, mycotoxins produced by various types of fungi, each of which hasvarying toxicity, in general chronic causes mycotoxicity. Mycotoxins have caused several types of diseasesin humans and animals. Aflatoxin B1 (AFB1) is a potential toxin as a hepatocarcinogen. Eating foods taintedwith AFB1 can cause acute (short term) and chronic (moderate or long term) poisoning; chronic disorderssuch as disorders of the central nervous system, cardiovascular and lung systems, and digestive tract. Somemycotoxins are carcinogenic, estrogenic, mutagenic, teratogenic, and immunosuppressive. The purpose ofthis study is the characterization of Aflatoxin B1 Biomarkers as Preference for Antitoxin Candidates forBiosensors for Halal Food Supply. The method of this research is AFB1 induction in mice, observed for 14days, on the 14th day liver organs were taken. The liver is prepared into organ extracts, analyzed using IHC.From the research results obtained protein expression in the liver organs of experimental animals by the IHCmethod. Further research is needed as an antitoxin and biosensor.